Potential of biofuels from algae: Comparison with fossil fuels, ethanol and biodiesel in Europe and Brazil through life cycle assessment (LCA) - Carneiro, Maria Luisa N.M.; Pradelle, Florian; Braga, Sergio L.; Gomes, Marcos Sebastião P.; Martins, Ana Rosa F.A.; Turkovics, Franck; Pradelle, Renata N.C. (Renewable & sustainable energy reviews, 2017)
Despite a substantial literature using life cycle assessment (LCA) approach, the extent to which second and third generation biofuels are more sustainable than the first generation remains a subject of debate. Although the existence of limitations due to LCA variability and uncertainty, this paper intends to determine global tendencies based on a statistic and critical interpretation of previously published study results, reviewing 61 recent papers addressing an environmental evaluation of microalgae biofuels. Such information is compared to the same impact indicators for fossil fuels and for ethanol and biodiesel from terrestrial crops in Europe and Brazil. For each case, the system boundaries and the methodological choices were precisely described. The sustainability potential of all biofuels was evaluated by the Global Warming Potential (GWP), the Energy Ratio (ER) and the Land Use (LU), allowing a broad estimation of the biofuels’ contribution to climate change mitigation, their net energy efficiency and their competiveness with food production chain. The results highlight that algae-derived biodiesel is, by far, the most efficient alternative in terms of land use compared to other biofuels, avoiding competition with food crops. Some biodiesel pathways can also satisfactorily perform in terms of greenhouse gases emissions reduction, but some others can be even worst than fossil diesel. Nevertheless, in terms of energy efficiency, algae biofuels cannot compete with other biofuels or fossil fuels. They present very low performances, even demanding more energy for its production then the energy they can deliver. Moreover, no pathway can be conclusively selected as preferable between the two main technologies available for microalgae biodiesel due to high uncertainties. However, open raceway pounds technology seems to be preferable as it looks less GHG intensive, requiring lower energy input and land use. Energetic and GWP performances can be improved if production pathways are carefully chosen and optimized.